(untitled) (Journal of Sciences & Technology, 2021)
NDT Magnetic measurements as impedance in Eddy currents, corecitif and residual field in hysteresis loop are used to study the different stages of mechanical alloying in the Fe–Co system. In this paper, we changed the electromagnetic properties of Fe-Co, by developing their metallurgical parameters such as grain size. For this we are used a planetary ball mill, we are milled the FeCo alloy for different milling times until to obtain nanostructure, the lamellar structure with some small particles embedded in them was observed during the first stage of mechanical alloying. XRD patterns show after 10 h of milling the formation of a disordered solid solution having a body-centered cubic (bcc) structure. After 40h of milling, morphological studies indicated that the average crystallites size is around 15 nm.